Children of the Jacaranda tree [compact disc, unabridged] : a novel - Delijani, Sahar, 1983- (Brilliance Audio, Inc., 2013)
Children of the Jacaranda Tree moves from the nightmarish reign of terror and secret prisons, to the birth of Iran's post-revolutionary generation, the children of the detained, repressed, and persecuted, through the first ripples of new dissent some thirty years later. At the lush and captivating center is a single tragedy which leaves both the begetters of the revolution and their children permanently scarred and traumatized.